Online English language learning among tertiary students - Alpino Susanto; Karunia Yulinda Khairiyah; Zalmi Dzirrusydi; Sri Sugiharti (Journal of Education and Learning (EduLearn), 2022)
The online learning in English language has been going along with the rapid development and diffusion of the information and communication techologies and shifted from being merely marginal trend to become popular, where the number of higher education institutions has dramatically increased to offer and led to extremely changes many aspect in learning societies. This study explores the technical abilities, technology accessibility and self-directed learning that contribute to student attitudes towards online English learning in predicting the continuance intention of the online learning. This study employed quantitative approach. There were 10 tertiary students interviewed as preliminary study, then 36 students were surveyed through questionnaire in a pilot test. The validated questionaire were used in this study on the 102 students. Rasch measurement model was utilized to validate the 25 items of questionnaire, meanwhile the Smart PLS ver. 2.0 was used to assess the regression of exogen to endogen variables. The study concluded that self- directed learning contributed to the attitude towards online English language learning as mediator to continuance intention of online learning. The ability and positive attitude in using digital technology must be present to support English learning current and forthcoming. The next research can focus more on how students adapt to a variety of rapidly changing technologies to support their English skills.